Single-nucleotide polymorphism panels in the racial authentication of Hairless pigs in Mexico - Lemus-Flores, Clemente; De la Cruz , Carlos; Borrayo, Juan; Orozco, María (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Massive genotyping panels of single-nucleotide polymorphisms (SNPs) were evaluated to create an authentication and racial identification strategy for the Hairless pig. Three populations of Hairless pigs from the states of Nayarit (n=10), Oaxaca (n=10) and Yucatán (n=143), Mexico, were genotyped with the porcine-GGP-50K chip, and genotypes for the Duroc (n=66), Hampshire (n=33), Landrace (n=95), Large White (n=47), Pietrain (n=42) and Iberico hairless (n=15) breeds were added. Three strategies involving previously reported SNP panels and a fourth strategy involving the combination of all SNP panels was evaluated. Using canonical discriminant analysis (CDA), the canonical correlations and percentages of racial discrimination were obtained, and with the first two canonical variables, distance trees between populations were constructed. Racial separation was achieved with all four strategies; the greater the number of SNPs used, the better the identification of the Hairless pig. The combined panel with 96 SNPs achieved 100 % racial assignment and had the greatest canonical correlation in the CDA, revealing a racial grouping of the three Hairless pig populations close to the Iberian population. With SNP panels, it is possible to achieve the racial authentication of the Hairless pig and discriminate it from other pig breeds.